Isolation, Characterization, and Antimicrobial Susceptibility of Escherichiacoli from Breeder Superior Native Chicken (KUB)in Yogyakarta, Indonesia - Suwito, Widodo; Andriani; Primatika, Roza Azizah; Tangkonda, Elisabet; Primatika, Roza (Jurnal Ilmu-Ilmu Peternakan, 2025)
Colibacillosis remains a prevalent issue in breeder superior native chickens (KUB). This study aims to isolate, characterize, and assess the antimicrobial susceptibility of E. coli from breeder KUB chickens in Yogyakarta, Indonesia. Samples, including infertile eggs (n=113), day-old chick (DOC) deaths (n=53), drinking water (n=17), feed (n=25), eggshells (n=117), and fluff (n=113), were collected through random sampling from breeder KUB chickens. Isolation and identification of E. coli were carried out via biochemical methods, whereas serological tests were performed with antisera for O1:K1, O2:K1, and O78:K80. Hemolytic E. coli strains were identified through culture on blood agar, and antimicrobial susceptibility was evaluated via the disk diffusion method. A total of 31 E. coli isolates were obtained from various sources: infertile eggs (15.04%), DOC-contaminated eggs (13.20%), drinking water (35.29%), feed (8.00%), eggshells (8.00%), and fluff (20.25%). Among the isolates, 22.62% were hemolytic, and 77.38% were nonhemolytic. The serotype distributions were as follows: 11.9% O1:K1, 9.52% O2:K1, and 9.52% O78:K80. E. coli isolates were susceptible to tetracycline, oxytetracycline, enrofloxacin, and sulfamethoxazole but resistant to ampicillin, streptomycin, and erythromycin. E. coli, the causative agent of colibacillosis, has been isolated from KUB breeder chickens in Yogyakarta. Therefore, strengthening biosecurity measures and implementing effective antibiotic management strategies are crucial for mitigating the risk of antibiotic resistance.